The effectiveness of cognitive-behaviour therapy in improving psychological adjustment to spinal cord injury : a review of the literature - Abdinor, Nicolette Jeanne (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2004.